The Paradoxes of modernity in J. R. R. Tolkien's fantasy (1917-1949) (TEL Tempo, Espaço e Linguagem, 2022)
The recurring themes in J. R. R. Tolkien's fantastic fiction – decadence, disenchantment, tragedy and menace – are a portrait of his time and, above all, an acute and conservative critique of the modern world and the rationalist pretensions that generated it. The author wanted to demonstrate, in literary terms, that the Enlightenment project had, in itself, the germ of its own destruction.Keywords: XXth century, modernity, fantasy, Tolkien, conservatism.